RUSSIAN LITERATURE - Raufova Ozoda (Journals Park Publishing, 2023)
At the beginning of the 19th century, Russian literature experienced the positive influence of classicism and sentimentalism and was enriched with new themes and genres, artistic images and creative techniques. Into you came a wave of pre-romantic movement aimed at creating and responding to the needs of a new age, a literature that was national in form and content. Artistic development our nation and society. At the same time, literary ideas, various philosophical, political and historical concepts formed in Europe at the end of the 19th century began to widely enter Russia. It will be discussed about the Russian literature.
Keywords: Russian literature, literary ideas, historical concepts, sentimentalism, classicism, genres.